Legal Perspective on Traditional & Naturopathy Regulatory Framework in Africa - (:unkn) unknown (My University, 2025)
This book, Legal Perspective on Traditional & Naturopathy Regulatory Framework in Africa, delves into the legislative and regulatory landscape surrounding traditional and naturopathic medicine across the African continent. As demand for alternative therapies grows, African countries face the challenge of balancing cultural traditions with the need for effective healthcare oversight. This work explores how legal frameworks, policies, and definitions for traditional and naturopathic medicine differ across Africa's five regions: Northern, Central, Southern, Eastern, and Western Africa.Drawing from extensive research on health laws and policies, the book examines key regulatory aspects, including practitioner licensing, and public health safety. Southern African countries stand out with more developed regulatory structures, often recognizing naturopathy within allied health professions. In contrast, other regions largely incorporate these practices within broader public health laws or unified traditional medicine acts. These disparities impact the quality of care, patient safety, and access to naturopathic and traditional treatments across the continent.This book provides a comparative analysis of existing frameworks, identifying best practices and legislative gaps that could inform future policies. By examining country-specific laws and regional trends, the book offers valuable insights for policymakers, legal practitioners, healthcare professionals, and scholars. It underscores the potential of a well-structured regulatory environment to enhance healthcare delivery, ensuring that naturopathic and traditional medicine practices support public health goals while respecting Africa’s rich cultural heritage.
Keywords: African Research